(untitled) (Jurnal Sustainable, 2022)
Education is one of the sectors that has been significantly affected by the Covid-19 pandemic. In the past, education was mostly done by learning in class or face-to-face, but when there was a pandemic, education was mostly done online which was bridged by gadgets. In addition, if the teaching and learning process is carried out directly, it will be divided into schedules to avoid crowds. Changes in education then make schools, teachers and students have to be able to adapt, especially in special schools that have students with special needs considering the process of teaching children with special needs is not easy. This research examines the strategies and innovations carried out by special schools in the Province of Bangka Belitung Islands. The research method used is a qualitative research method by using the sociological perspective of education to analyze the results of the research. The conclusion shows that during the pandemic, special schools in the province of Bangka Belitung Islands made adaptations and innovations in teaching and learning activities adapted to pandemic conditions. Adaptations and innovations carried out include learning carried out at home, dividing schedules or incoming shifts for students, forming groups of covid response officers whose members involve students, making drinks to ward off Covid from school gardens and others.